International Communication of Traditional Chinese Medicine in the Context of COVID-19 Pandemic by Analogy of Directional Solidification - Yingwen Cai; Xueyong Shen (Wolters Kluwer Health/LWW, 2020)
According to the phenomenon-taking of classified analog, directional solidification can be an excellent approach for international communication of traditional Chinese medicine (TCM) in the context of COVID-19 pandemic. Attitudes toward TCM by Western Medicine (WM) can be represented by various morphologies of the solid/liquid interface. COVID-19 has created an urgent need for the worldwide spread of TCM. To counter any doubts and objections against TCM, COVID-19 pandemic provides a good opportunity, meanwhile a steady and firm pace forward should be kept. It is also necessary to resolve domestic controversies and to lower cultural shock. The philosophy of TCM can agree fairly well with dialectical materialism; the scientific connotation of pentacy in TCM can be explained through the symptoms of COVID-19-infected patients. A TCM understanding compatible with WM will accelerate its international acceptance, which could help to better elaborate the significance of humanity in TCM. Holistic medicine under the guidance of TCM principles is an important trend in medical development, whose framework is illustrated in a 4C+T diagram.